Continuous phenol removal using a liquidâsolid circulating fluidized bed - Sureshkumar, N. (MDPI AG, 2020)
A liquid-solid circulating fluidized bed (LSCFB) helps to overcome the shortcomings of conventional fluidized beds by using a particle separation and return system as an integral part of the overall reactor configuration. Batch adsorption experiments were carried out for the removal of phenol from a synthetically prepared solution using fresh activated-carbon-coated glass beads. The morphological features and surface chemistry of the adsorbent were analyzed via SEM and FTIR techniques. The adsorbent dosage, contact time and temperature were varied along with solution pH to assess their effects on the adsorbent performance for phenol removal. Isotherm modeling showed that the phenol removal using the activated-carbon glass beads followed the Langmuir model. Effectively, it was observed at an adsorbent loading of 2.5 g/150 mL of feed volume and a contact time of 3 h produced an 80 efficiency in the batch study. Furthermore, on scaling it up to the column, the desired 98 phenol-removal efficiency was obtained with an adsorbent dosage of 250 g and contact time of 25 min. Adsorbent regeneration using 5 (v/v) ethanol showed a 64 desorption of phenol from the sorbent within 20 min in the LSCFB. Â© 2020 by the authors. Licensee MDPI, Basel, Switzerland.